The musical works of Tobias Zeutschner (1621-75), as documented in occasional school prints. Working on a thematic catalogue of the Breslau [Wroclaw] Organist - Halamska, Paulina (Interdisciplinary Studies in Musicology, 2018)
Tobias Zeutschner (b. 1621, d. 1675), organist of St Mary Magdalene’s in Breslau, was not a teacher at the Magdalenaeum gymnasium school affiliated to that church. However, occasional prints preserved in the Silesian-Lusatian Collection of Wroclaw University Library confirm his active participation in the musical life of that school. Until now, the scenarios of plays performed by the Magdalenaeum’s pupils have never been the object of musicologists’ interest. And yet they allow us to add several previously unknown, albeit not extant, items to Zeutschner’s oeuvre. Consequently, the thematic catalogue of compositions by Tobias Zeutschner (prepared by the author) contains 83 items, as compared to the 47 listed by Reinhold Starke in 1900. At least ten of the new titles were noted in the school’s occasional prints. What is more, the Magdalenaeum pamphlets offer additional information about known compositions that is particularly helpful in establishing their chronology. For example, previously we had only an approximate date for the Christmas biblical history ‘Halleluja, höret an die Geburt unsers Herren’, a major work by Zeutschner, whereas now it is possible to propose 29 January 1660 as the date of its first rendition.